Impact of in vitro fertilization‐embryo transfer on mother‐to‐infant transmission in women with chronic HBV infection. (1st July 2022) - Yi, Wei; Li, Minghui; Sun, Fangfang; Lu, Huihui; Zeng, Zhan; Bi, Xiaoyue; Yang, Liu; Lin, Yanjie; Cao, Xiuzhen; Hu, Yuhong; Zhou, Mingfang; Zhang, Lu; et al.
Abstract: Background and Aims: In vitro fertilization‐embryo transfer (IVF‐ET) may increase the risk of mother‐to‐child transmission (MTCT) of hepatitis B virus (HBV). The purpose of this study was to investigate the impact and safety of IVF‐ET on MTCT in women with chronic HBV infection (CHB). Methods: The data of 298 women who got pregnant by IVF‐ET and their 375 children were collected retrospectively. Mothers were divided into the CHB group ( n  = 224) and the control group (HBsAg negative, n  = 74). After birth, newborns were routinely vaccinated with the hepatitis B vaccine, and infants in the CHB group were injected with hepatitis B immunoglobulin within 2 h after birth. Demographic information, clinical data and laboratory test results were collected. The primary outcome measures were the MTCT rate of HBV, and the secondary outcome measures were the safety of the mother and infant. Results: There was no case of HBV MTCT in all 282 newborns born in the CHB group and 93 neonates born in the control group. Of the two groups, the birth weight (3056.74 ± 601.65 vs. 2926.24 ± 704.86, P  = .083), length (49.22 ± 1.97 vs. 48.74 ± 3.09, P  = .167), 5‐min Apgar score (9.97 ± 0.21 vs. 9.90 ± 0.51, P  = .212), days of pregnancy (265.70 ± 12.73 vs. 262.02 ± 17.50, P  = .064) and neonatal malformation rate (0.71% vs. 0, P  = 1.000) were similar. Two cases of neonatal malformation occurred in the CHB group. The incidences of pregnancy and childbirth complications were similar between the two groups. Conclusion: IVF‐ET does not increase the risk of MTCT in women with chronic HBV infection, and it is safe for mothers and infants.